2006
DOI: 10.1093/nar/gkj519
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional regulation of thioredoxin by the stress inducible heterogenous ribonucleoprotein A18

Abstract: Thioredoxin (TRX) is a key protein of the cellular redox metabolism, which expression is increased in several tumors especially gastric tumors. Even though ultraviolet (UV) and hypoxia specifically induce TRX, the mechanisms that lead to increased TRX levels are still ill defined. Here, we show that the heterogenous ribonucleoprotein A18 (hnRNP A18) RNA Binding Domain (RBD) and the arginine, glycine (RGG) rich domain can bind TRX 3′-untranslated region (3′-UTR) independently but both domains are required for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(119 citation statements)
references
References 37 publications
3
116
0
Order By: Relevance
“…Although in DSS-induced colitis, Cirp protein was not detected in the blood (data not shown), it is conceivable that Cirp released from injured epithelial cells could function as damage-associated molecular pattern molecules in situ to activate NF-kB in immune cells of the colon. Furthermore, Cirp can bind the 3 0 untranslated region of specific transcripts to stabilize them and thus facilitate their transport to ribosomes for translation (22)(23)(24). Cirp might regulate the expression of cytokines and antiapoptotic genes posttranscriptionally as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in DSS-induced colitis, Cirp protein was not detected in the blood (data not shown), it is conceivable that Cirp released from injured epithelial cells could function as damage-associated molecular pattern molecules in situ to activate NF-kB in immune cells of the colon. Furthermore, Cirp can bind the 3 0 untranslated region of specific transcripts to stabilize them and thus facilitate their transport to ribosomes for translation (22)(23)(24). Cirp might regulate the expression of cytokines and antiapoptotic genes posttranscriptionally as well.…”
Section: Discussionmentioning
confidence: 99%
“…Cirp is induced by cellular stresses such as UV irradiation and hypoxia (19)(20)(21). In response to the stress, Cirp, which migrates from the nucleus to the cytoplasm, affects posttranscription expression of its target mRNAs (22)(23)(24) and functions as a damageassociated molecular pattern molecule that promotes inflammatory responses when present extracellularly (25). Cirp also affects cell growth and cell death induced by TNFa or genotoxic stress (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…The cold inducible protein CIRP, also known as heterogenous ribonucleoprotein A18, shares high homology with RBM3, especially in the RRM (Lleonart, 2010). lt has recently been found to induce the expression of thioredoxin and thereby protecting cells from oxidative stress and apoptosis through quenching reactive oxygen species (Yang et al, 2006). Furthermore, a role for CIRP has recently been established in preserving the stemness of neural stem cells and suppressing apoptosis of the cells in conditions of moderate low temperature (32°C) (Saito K. et al, 2010).…”
Section: Vector-based Rbm3 Over-expression Mimics the Protective Effementioning
confidence: 99%
“…In spinach (Spinacia oleracea), four isoenzymes of chloroplastic ascorbate peroxidase are known to be encoded by a single gene and the corresponding mRNAs are reportedly generated by AS (Shigeoka et al, 2002). Alternatively spliced forms of the genes whose expression is affected by stress (such as protein phosphatase 2C) and those showing antioxidant activity (such as carbonic anhydrase) have been identified (Slaymaker et al, 2002;Meskiene et al, 2003;Yang et al, 2006). We also observed that most of the ESTs correspond to two or more (in a few cases) gene models, indicating that gene duplication events have occurred in Populus (Jansson and Douglas, 2007).…”
Section: Investigation Of As In the Populus Ros Gene Networkmentioning
confidence: 99%